Resgate e propagação vegetativa de Lecythis pisonis Cambes por estaquia - Bernardes, Vanessa Pimentel (2016)
Sapucaia (Lecythis Pisonis Camb.) is a native specie that has a long juvenility period, short seed viability and difficulty to collect fruit, characteristics that justify the vegetative propagation techniques studie such as cuttings. Therefore, the main objective of the present study was to evaluate the root formation capacity in steems cuttings treated with indole-3-butyric acid (IBA), obtained of eight trees of sapucaia specie located in the Espírito Santo state, as well as to evaluate the technique efficiency of vegetative rescue using outstanding branches ofadult trees. The research was divided into two experiments, being that in the first it was aimed to assess the rooting potential of herbaceous and semi-woody cuttings (with leaves) of 7cm to 12 cm of length taken from mother trees in transition phase located in the Jerônimo Monteiro municipality, and adult mother trees located in Cachoeiro de Itapemirim, Alegre and Linhares municipalities, being that the mother trees of the latter municipality, beyond of the previous cuttings were made woody cuttings (without leaf). The cuttings were treated using IBA (0; 2000; 4000; 6000 and 8000 mg Kg-1 ) and followed a randomized block design with four replicates and 10 cuttings per plot. After 120 days in a greenhouse, under irrigation system of intermittent type was analyzed the callus percentage and cuttings survival. The data were submitted to variance analysis to verify if there is significant difference between the means, and if the factors have influence on some dependent variable. In the second experiment evaluated the emission of epicormic sprouts in outstanding branches of adult trees selected to the previous experiment. Thereunto, branches of 60 cm of length, removed of the tree top, were sectioned and carried to the greenhouse, where remained for 60 days. After this period, was observed the number of epicormic sprouts formed on the branches. The results showed mortality of the herbaceous andsemi-woody cuttings, however, one herbaceous cuttings obtained of juvenile mother tree remains alive and with leaf, being the only with the presence of root, and of this same mother tree 80.5% of herbaceous cuttings had the presence of callus. Was observed 52.75% of woody cuttings survivors of adult mother trees. It is concluded that premature leaf fall in herbaceous and semi-woody cuttings favors the mortality of the same, while the woody cuttings present high percentage of survival. The IBA concentrations had no significant effect on the callus formation of juvenile herbaceous cuttings and in the survival of woody cuttings of adult mother trees. The vegetative material used in the juvenility rescue proved be feasible for the sprouts formation, however, rooting potential of sprouts must be assessed.